Unveiling Dynamics and Complexity : 13th Conference on Computability in Europe, CiE 2017, Turku, Finland, June 1216, 2017, proceedings /: 13th Conference on Computability in Europe, CiE 2017, Turku, Finland, June 1216, 2017, proceedings. ([2017]) - Unknown
No abstract available